Traumatyczne doświadczenie wojny i emigracji. Arturo Barea (1897–1957) - Bender, Elżbieta (Acta Neophilologica, 2025)
Through an analysis of the prose of the Spanish writer Arturo Barea, the article discusses the issue of emigration caused by the Civil War of 1936–1939. In several of Barea’s works, we learn about the complicated situation of a refugee who must face traumatic memories of the war, along with the difficulties in adapting to the new post-war reality. Emigration is associated with a longing for one’s homeland and family. Moreover, it may often create a sense of failure in life. Years later, when a refugee returns to the country of origin, a feeling of alienation arises due to the experience of being “out-of-time”. There is only one short story in which Barea presents a positive picture of life in exile.